Management of Teaching and Educational Staff in Improving Performance at SMP Islam Al-Muammilin Karangampel Indramayu - Muhammad Ibnu Ubaidilah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Teaching and educational staff are vital components in delivering quality education in an increasingly competitive global era. SMP Islam Al-Muammilin Karangampel, as an Islamic-values-based private institution in Indramayu Regency, continuously strives to improve its human resource management quality to achieve optimal performance. This study aims to: (1) describe the implementation of teaching and educational staff management in improving performance at SMP Islam Al-Muammilin Karangampel; and (2) identify supporting and inhibiting factors influencing such management implementation. This research employed a qualitative descriptive approach with data collected through non-participant observation, in-depth interviews, and documentation studies. Research subjects included the principal, vice-principal, teachers, and head of administration. Data analysis used Miles and Huberman's interactive model comprising data reduction, data display, and conclusion drawing. Results show that: (1) Teaching staff management at SMP Islam Al-Muammilin is implemented through five main stages: needs-based planning, selective recruitment, multi-stage selection, human resource development through internal and external training, and periodic performance evaluation. School performance involves input components (teaching materials, methodology, facilities, conducive atmosphere, decision-making, program planning, institutional management, learning processes, and evaluation) and output components (academic and non-academic achievements); (2) Supporting factors include solid teamwork, high internal motivation, active parental involvement, harmonious communication, and effective principal leadership. Inhibiting factors include lack of discipline among some teaching staff, limited facilities and infrastructure, insufficient reference books, teachers teaching outside their expertise, and confusion regarding curriculum implementation.